2022
DOI: 10.1108/ijchm-10-2021-1280
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative switching barriers: promoting hotel customer citizenship behaviour through brand attachment

Abstract: Purpose This study aims to develop and test a theoretical model postulating that a hotel customer’s brand attachment is reinforced by positive and negative switching barriers, which, in turn, determine customer citizenship behaviour (CCB) towards hotel brands. Design/methodology/approach Surveys were conducted and completed by 233 respondents in the USA who had favourite hotel brands and used these brands in the previous year. A framework was developed based on the literature, and eight hypotheses were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…First, prior research has identified and examined various types of negative switching barriers such as financial switching cost, relational switching costs and procedural switching costs (Blut et al , 2015; Jones et al , 2007; Lee and Kim, 2022). However, little is known about the role of the service contract itself as a type of switching cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, prior research has identified and examined various types of negative switching barriers such as financial switching cost, relational switching costs and procedural switching costs (Blut et al , 2015; Jones et al , 2007; Lee and Kim, 2022). However, little is known about the role of the service contract itself as a type of switching cost.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Malhotra and Malhotra (2013) investigated social network effects as a positive switching barrier and unreasonable contract length as a negative switching barrier. However, Lee and Kim (2022) divided switching barriers into positive barriers (i.e. social benefit, confidence benefit and special treatment benefit) and negative barriers (i.e.…”
Section: Literature Review and Hypotheses’ Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Brand attachment is an overall evaluation of the brand, which includes affection for relationships. Lee and Kim (2022) claimed that brand attachment positively influences the value of the products. Thomson, MacInnis, and Whan Park (2005) conceptualized brand attachment using three dimensions: affection, passion, and connection.…”
Section: Brand Attachmentmentioning
confidence: 99%
“…Incorporating the theory with switching barriers can offer researchers a more profound comprehension of how customers alter their online hotel booking behaviors. Relational investment focuses on personal bonds developed between consumers and service providers (Lee and Kim, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%